2014
DOI: 10.1007/s11356-014-2980-y
|View full text |Cite
|
Sign up to set email alerts
|

Faecal pollution loads in the wastewater effluents and receiving water bodies: a potential threat to the health of Sedibeng and Soshanguve communities, South Africa

Abstract: The discharge of untreated or inadequately treated effluents has been identified among the activities responsible for the spread of a wide range of potentially infectious agents. The aim of this study was to determine whether inadequate treatment of wastewater and the faecal pollution load of effluents and receiving water bodies in Sedibeng District and Soshanguve peri-urban area of the Tshwane Metropolitan Municipality could be a potential threat to the health of the surrounding communities. Variations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 37 publications
0
25
0
1
Order By: Relevance
“…The presence of indicator bacteria in waterbodies does not pose a direct risk of waterborne diseases, but their presence indicates faecal contamination and the possible presence of waterborne pathogens (Burres 2009;Teklehaimanot et al 2014). Risk of waterborne disease outbreaks also depends on water uses, such as consumption and recreational activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of indicator bacteria in waterbodies does not pose a direct risk of waterborne diseases, but their presence indicates faecal contamination and the possible presence of waterborne pathogens (Burres 2009;Teklehaimanot et al 2014). Risk of waterborne disease outbreaks also depends on water uses, such as consumption and recreational activities.…”
Section: Discussionmentioning
confidence: 99%
“…Although FIB are generally not harmful themselves, their presence in water body indicates the possible presence of other pathogenic microorganisms (Burres 2009). Indicators are useful in assessing health risk, regardless of whether the specific pathogens are pathogenic or not (Wu et al 2011;Teklehaimanot et al 2014). E. coli, faecal coliforms and faecal streptococci have been most commonly used as microbial indicators of faecal contamination in water bodies.…”
Section: Introductionmentioning
confidence: 99%
“…These methods have high sensitivity, specificity, and speed. The methods used for V. cholerae detection by conventional PCR and/or real-time PCR are well established (Wang et al, 2007;Tebbs et al, 2011;Teklehaimanot et al, 2014). Many research studies have identified Vibrio cholerae strains using 16S rRNA sequencing, pulsed-field gel electrophoresis (PFGE), nested and multiplex PCR (Chakraborty et al, 1999;Kong et al, 2002;Tarr et al, 2007;Mendes et al, 2008;Keshav et al, 2010).…”
Section: Molecular-based Methodsmentioning
confidence: 99%
“…In the study by [32] the tolerance of E. coli CGMCC to 10 mg/L chlorine dose was observed with only 4.0 log reduction achieved in a bacterial population of approximately 10 7 colony forming units (CFU/mL). In South Africa, studies have demonstrated a strong correlation between E. coli survival and low chlorine residuals [33][34][35]. For example, in the Eastern Cape, South Africa, [36] recovered E. coli strains in wastewater effluents containing low chlorine residuals ranged between 0.05 and 0.24 mg/L.…”
Section: Introductionmentioning
confidence: 99%